The Complete Genome and Physiological Analysis of the Microbialite-Dwelling Agrococcus pavilionensis sp. nov; Reveals Genetic Promiscuity and Predicted Adaptations to Environmental Stress - White, Richard Allen; Gavelis, Greg; Soles, Sarah A.; Gosselin, Emma; Slater, Greg F.; Lim, Darlene S. S.; Leander, Brian; Suttle, Curtis A. (Frontiers in Microbiology, 2018)
Members of the bacterial genus Agrococcus are globally distributed and found across environments so highly diverse that they include forests, deserts, and coal mines, as well as in potatoes and cheese. Despite how widely Agrococcus occurs, the extent of its physiology, genomes, and potential roles in the environment are poorly understood.. Here we use whole-genome analysis, chemotaxonomic markers, morphology, and 16S rRNA gene phylogeny to describe a new isolate of the genus Agrococcus from freshwater microbialites in Pavilion Lake, British Columbia, Canada. We characterize this isolate as a new species Agrococcus pavilionensis strain RW1 and provide the first complete genome from a member of the genus Agrococcus. The A. pavilionensis genome consists of one chromosome (2,627,177 bp) as well as two plasmids (HC-CG1 1,427 bp, and LC-RRW783 31,795 bp). The genome reveals considerable genetic promiscuity via mobile elements, including a prophage and plasmids involved in integration, transposition, and heavy-metal stress. A. pavilionensis strain RW1 differs from other members of the Agrococcus genus by having a novel phospholipid fatty acid iso-C15:1Δ4, β-galactosidase activity and amygdalin utilization. Carotenoid biosynthesis is predicted by genomic metabolic reconstruction, which explains the characteristic yellow pigmentation of A. pavilionensis. Metabolic reconstructions of strain RW1 genome predicts a pathway for releasing ammonia via ammonification amino acids, which could increase the saturation index leading to carbonate precipitation. Our genomic analyses suggest signatures of environmental adaption to the relatively cold and oligotrophic conditions of Pavilion Lake microbialites. A. pavilionensis strain RW1 in modern microbialites has an ecological significance in Pavilion Lake microbialites which include potential roles in heavy-metal cycling and carbonate precipitation (e.g., ammonification of amino acids and filamentation which many trap carbonate minerals).